Pendampingan Dirosah Ula Pimpinan Cabang Majelis Dzikir dan Sholawat Rijalul Ansor Kabupaten Wonosobo tahun 2023 - Alfan Nurngain; Hilmy Pratomo; Robingun Suyud El Syam (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The purpose of this article is to convey what the Dirosah Ula mentoring of the Branch Leadership of the Rijalul Ansor Dzikir and Sholawat Assembly of Wonosobo Regency is like in 2023. The service strategy is through three things, namely: coordination, implementation, and Focus Group Discussion. The article is a field research with a qualitative approach, collecting data through observation, interviews, and documentation. The results of this activity show that Dirosah Ula is very beneficial for participants in strengthening their souls and knowledge so that they are more mentally and scientifically prepared in fighting for the development of Nahdlatul Ulama. This contributes to the welfare of the people. The conclusion focuses on the importance of cadreship in the young NU cadre environment and its contributions and implications for the spread of the teachings of Ahlussunnah wal Jama'ah an-Nahdliyah